SINTESIS NANOPARTIKEL PERAK MENGGUNAKAN BIOREDUKTOR EKSTRAK DAUN KITOLOD (Hippobroma longiflora (L.) G.Don.) DAN APLIKASINYA PADA FOTODEGRADASI METIL JINGGA - Silvia Sukmawati; Devi Indah Anwar; Lela Lailatul Khumaisah (Fakultas Teknik Universitas Wahid Hasyim, 2025)
wastewater, which can disrupt aquatic ecosystems by inhibiting microalgae photosynthesis. One effective and eco-friendly method for treating MO wastewater is photocatalytic degradation using silver nanoparticles (AgNPs). AgNPs are considered capable of degrading dyes at high concentrations. This study aims to synthesize AgNPs using Hippobroma longiflora (L.) G.Don (kitolod) leaf extract as a bioreductor and to evaluate its effectiveness in the photocatalytic degradation of MO. The synthesis of AgNPs was carried out using a green synthesis method via reduction of polyol compounds present in the kitolod leaf extract. The obtained AgNPs were characterized using UV-Vis, FT-IR, XRD, SEM-EDX, and DRS UV-Vis. The formation of AgNPs was indicated by a color change to brownish-black and a UV-Vis absorption peak at 434 nm. FT-IR results confirmed the role of phenolic compounds from the kitolod leaf extract in reducing Ag⁺ to Ag⁰. XRD analysis revealed an average crystallite size of 56.33 nm, while SEM images showed spherical morphology. The DRS-UV analysis determined a band gap value of 3.04 eV. The highest photocatalytic efficiency of AgNPs in degrading 200 ppm MO was achieved at pH 2, with 5 mg of AgNPs and 4 hours of irradiation, yielding a degradation percentage of 50.87%.